2018
DOI: 10.1089/vio.2017.0041
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Among Transgender Youth: Associations with Intrapersonal and Structural Factors

Abstract: Intimate partner violence (IPV) is a serious public health problem, linked with a number of poor health outcomes. Some research demonstrates that transgender and gender nonconforming (TGNC) youth may experience IPV at similar rates to heterosexual cisgender women; however, there is a dearth of data examining the experiences of IPV among this population. The exclusion of TGNC youth in IPV research and public health interventions is problematic because it contributes to a traditional gender-based heterosexual mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 37 publications
0
32
1
1
Order By: Relevance
“…However, being uninformed about sex before its enactment negates the possibility for consent, which is deeply concerning, especially in light of the disproportionately high rates of sexual violence and intimate partner violence experienced by TNB youth. 13 When considering ideal content for a curriculum tailored to TNB youth, participants recognized the need for some topics that are already included in most standard sex education curricula-such as STI prevention, contraception, and relationships-but require reframing to be trans-inclusive. They also desired information that is unique to TNB youth (eg, dysphoria, non-medical and medical gender-affirming interventions), which warrants being covered and is not commonly touched on in existing curricula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, being uninformed about sex before its enactment negates the possibility for consent, which is deeply concerning, especially in light of the disproportionately high rates of sexual violence and intimate partner violence experienced by TNB youth. 13 When considering ideal content for a curriculum tailored to TNB youth, participants recognized the need for some topics that are already included in most standard sex education curricula-such as STI prevention, contraception, and relationships-but require reframing to be trans-inclusive. They also desired information that is unique to TNB youth (eg, dysphoria, non-medical and medical gender-affirming interventions), which warrants being covered and is not commonly touched on in existing curricula.…”
Section: Discussionmentioning
confidence: 99%
“…12 Additionally, in a 2015 sample of U.S. TNB youth, 45% of 187 youth surveyed reported a history of intimate partner violence. 13 Among young transgender women of color in the United States, >50% reported a history of forced sexual activity, sex in exchange for resources, and sex under the influence of drugs or alcohol. 14 In a Brazilian study, 32% of surveyed transgender women and men who have sex with men reported childhood sexual experiences with an older partner, with mean age at first experience being 9 years, and partners' average age of 19 years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, use during these formative years has been tied to increased rates of subsequent illicit drug use and use disorders (Lynskey et al, 2012), as well as suicidal ideation and personality disorders (Copeland et al, 2013). Within the context of minority stress theory, this potential dose-response relationship might reflect the increased levels of expected stress that youth of minority identities are known to experience given their reporting higher rates of emotional and physical violence (Goldenberg et al, 2018), depression (Day et al, 2017), suicidal ideation (Olson et al, 2015), and perceived lack of safety (Kosciw et al, 2016) acting concomitantly with lowered levels of resilience producing an increased engagement in a risky coping behavior (i.e., cannabis use). Such patterns should be studied in greater depth across more robust cannabis using profiles (e.g., occasional vs. problematic user), but generally these findings would support the need for health care providers and practitioners to help support and develop resilience for these vulnerable youth groups; suggestions for which we offer later in the discussion.…”
Section: Discussionmentioning
confidence: 99%
“…However, members of gender and sexuality diverse communities experience DVA differently and have different needs (Turell and Cornell-Swanson, 2005). TNB people in particular experience significantly higher rates of intimate partner DVA across the lifespan than other populations (Barrett and Sheridan, 2017;Cook-Daniels and Munson, 2010;Goldenberg et al, 2018;Roch et al, 2010;Stotzer, 2009;Walker, 2015), including in Australia (Australian Institute of Health and Welfare, 2018; Campo and Tayton, 2015;Couch et al, 2007;Papazian and Ball, 2016). The negative impact of intimate partner DVA is increased by the exclusion of TNB people from dominant narratives surrounding DVA, due to cisgenderism, heteronormativity and, at times, the resultant pressure to remain 'closeted', which prevents TNB people from being identified as such by services (Greenberg, 2012;Holmes, 2016;Rogers, 2017).…”
Section: Transgender and Non-binary People's Experiences Of Violence mentioning
confidence: 99%
“…Over the last decade or so there has been greater inclusion of other animals in sociological research and some -within and without the discipline -have argued there is a need to take 'nonhuman animals seriously, treating them as aware actors on the social stage' (Birke, 2011: xx; see also, for example, Cudworth, 2016;Coulter, 2016;Gillespie, 2018;Hamilton and Taylor, 2017;Nibert, 2003;Peggs, 2013;Philo and Wilbert, 2000;Emel and Wolch, 1998). In this article we extend this focus by considering how animal companions themselves are at risk of violence when living in households with TNB people where abuse is present.…”
mentioning
confidence: 99%